1999
DOI: 10.1099/00207713-49-1-43
|View full text |Cite
|
Sign up to set email alerts
|

Treponema brennaborense sp. nov., a novel spirochaete isolated from a dairy cow suffering from digital dermatitis

Abstract: A novel Treponema species was isolated from an ulcerative lesion of a cow suffering from digital dermatitis (DD), a disease which causes painful ulcerations along the coronary band. Among other anaerobic bacteria, high numbers of spirochaetes have been regularly found in DD lesions. Here data are presented of a spirochaete isolated from a DD ulcer. By chemotaxonomy, protein analysis and comparative 165 rDNA sequence analysis this isolate was classified as a treponeme that differed from all Treponema species de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 12 publications
3
83
0
Order By: Relevance
“…1a) has been reported for other members of the genera Spirochaeta and Treponema (e.g. Fracek & Stolz, 1985;Schrank et al, 1999;Zhilina et al, 1996). Moreover, the cells of strain RASEN T had hook-shaped ends.…”
Section: H Imachi and Othersmentioning
confidence: 76%
“…1a) has been reported for other members of the genera Spirochaeta and Treponema (e.g. Fracek & Stolz, 1985;Schrank et al, 1999;Zhilina et al, 1996). Moreover, the cells of strain RASEN T had hook-shaped ends.…”
Section: H Imachi and Othersmentioning
confidence: 76%
“…2) revealed that the sequences of the endosymbionts were derived from spirochetes of the genus Treponema and belonged to the previously defined termite Treponema cluster II (26), which consists of the ectosymbionts attached to the cell surface of gut protists as far as their localizations were examined (27,28). This cluster formed a clade with saccharolytic treponemes that contained Treponema brennaborense, an isolate from a digital dermatitis ulcer of a cow (29), as a close cultured relative, but distantly related to the termite Treponema cluster I that comprises isolates and clone sequences from termite guts. We propose a species, "Candidatus Treponema intracellularis" for this previously unidentified endosymbiont (SI Text).…”
Section: Identification Of the Bacterial Endosymbiont Of Eucomonymphamentioning
confidence: 99%
“…Motile spirochaetes were also observed and successfully cultured [9,10]. Recently, spirochaetes have been cultured successfully from cases of a related disease of cattle, bovine digital dermatitis, in the USA [11], Germany [12] and the UK [13]. The latter study used immunomagnetic separation to isolate a spirochaete from affected cattle [13].…”
Section: Introductionmentioning
confidence: 99%